Validation of the Chinese Version of the Somatic Symptom Disorder–B Criteria Scale for Detecting DSM-5 Somatic Symptom Disorders: A Multicenter Study. Issue 3 (April 2020) - Li, Tao; Wei, Jing; Fritzsche, Kurt; Toussaint, Anne Christin; Jiang, Yinan; Cao, Jinya; Zhang, Lan; Zhang, Yaoyin; Chen, Hua; Wu, Heng; Ma, Xiquan; Li, Wentian; et al.
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: This study aimed to validate the Chinese version of the Somatic Symptom Disorder–B Criteria Scale (SSD-12) in an outpatient sample from Chinese general hospitals and to determine the diagnostic performance of the SSD-12 as a screening tool for somatic symptom disorder (SSD). Methods: The Chinese version of the SSD-12 was completed by 699 outpatients from nine general hospitals during a 16-month period (2016–2018). The SSD section of the Structured Clinical Interview for DSM Disorders, Fifth Edition, Research Version, was used to determine diagnostic accuracy (criterion validity). The construct validity of the SSD-12 was evaluated by examining correlations with the Whiteley Index-7, Patient Health Questionnaire-15, Patient Health Questionnaire-9, General Anxiety Disorder-7, World Health Organization Disability Assessment Schedule, and Medical Outcome Study 12-item Short Form Health Survey (SF-12). Results: The SSD-12 had excellent internal consistency in this sample (Cronbach α = .95). Confirmatory factor analyses replicated a three-factor structure that reflects the cognitive, affective, and behavioral aspects (Comparative Fit Index = 0.963, Tucker-Lewis Index = 0.952, root mean square error of approximation = 0.08, 90% confidence interval = 0.08–0.09), but was also consistent with a general one-factor model of the SSD-12 (Comparative Fit Index = 0.957, Tucker-Lewis Index = 0.948, root mean square error of approximation = 0.09, 90% confidence interval = 0.08–0.10). The optimal cutoff point for the Structured Clinical Interview for DSM Disorders–based diagnosis of SSD was 16 (sensitivity = 0.76, specificity = 0.80). The SSD-12 sum score was significantly associated with somatic symptom burden (Patient Health Questionnaire-15: r = 0.52, p < .001), health anxiety (Whiteley Index-7: r = 0.82, p < .001), depressive symptoms (Patient Health Questionnaire-9: r = 0.63, p < .001), general anxiety (General Anxiety Disorder-7: r = 0.64, p < .001), health-related quality of life (physical component score of SF-12: r = −0.49, p < .001; mental component score of SF-12: r = −0.61, p < .001), and health-related disabilities (World Health Organization Disability Assessment Schedule: r = 0.56, p < .001). Conclusions: Initial assessment indicates that the Chinese version of the SSD-12 has sufficient reliability and validity to warrant further testing in both research and clinical settings.